PENGARUH KONSENTRASI KINETIN TERHADAP PERTUMBUHAN SUBKULTUR PISANG KEPOK TIMBATU SECARA IN VITRO - Yuni Maulida; Nofia Hardarani; Hilda Susanti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
Kepok Timbatu bananas are a local food source that is not yet popular in the community. These bananas are rich in nutrients and contain high levels of starch. However, they are rarely cultivated and not widely found, resulting in a limited supply of planting materials. Therefore, propagation through in vitro culture, particularly during the subculture stage, is necessary. This study aimed to determine the best kinetin concentration for the in vitro growth of Kepok Timbatu banana subcultures. The study was designed a completely randomized design (CRD) with one factor, testing kinetin concentrations in MS medium at four levels: k1 = 3 mg L-1, k2 = 5 mg L-1, k3 = 7 mg L-1, and k4 = 9 mg L-1. Observations in this study include time of browning appearance, browning percentage (1-6 weeks after subculture), time of shoot emergence, number of shoots (1-6 weeks after subculture), time of root emergence, number of roots (3-6 weeks after subculture), number of leaves (3-6 weeks after subculture), and shoot height. The results showed that the kinetin concentration did not significant effect on all observed variables.